INTAKE AND DIGESTIBILITY OF DRY AND ORGANIC MATTER, AND CRUDE PROTEIN OF MALE BALI CATTLE FATTENED IN SMALLHOLDER FARMS - Tahuk, Paulus Klau; Dethan, Agustinus Agung; Sio, Stefanus (Journal of Tropical Animal Science and Technology, 2021)
The experiment was conducted for 3 months using nine (9) males Bali Cattle ages 2,5 - 3,5 or an average of 3.0 years old based on teeth estimated with initial body weight range is 227-290 kg or an average of 257.40±23,60 kg in the Fattening Stalls, Bero Sembada Farmers Group, Laen Manen Sub District, Belu Regency, East Nusa Tenggara. This research is adapted to the practice of ranchers in fattened cattle that includes management of feeding, housing, and health. The type of feed given during the study was Centrosema pubences, Clitoria ternatea, Fresh Corn Straw, Kinggras, Leucaena leucocepala, Natural Grass, Elephant Grass, and Turi. The results of the research showed that the Bali cattle male finishing phase on fattening with forage, yield dry matter intake (kg/head/day) reached 7.079 or 2.509 % of BW, while the crude protein and organic material intake respectively 1.053 and 6.440 (kg/head/day). Digestibility coefficients of dry matter were 56.68%, crude protein 69.86%, and organic matter 68.83%. It can be concluded that the use of forage on fattening male Bali cattle by ranchers was the produce dry matter intake, crude protein, and organic matter are high quite but gives relatively low digestibility.